New Challenges in Wood and Wood-Based Materials II - Kristak, Lubos; Réh, Roman; Kubovský, Ivan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Wood is a natural material that is available in large quantities and is easy to produce, making it the perfect material to consider for the circular economy. Its importance has dramatically increased in recent years. This increase is accompanied by the development of new research methods that open new possibilities in the areas related to wood and wood products in the process of their production, processing, and final use. The main topics of this Special Issue were the knowledge of the quality of wood and other lignocellulose materials; the processes of their effective utilization and processing for more efficient processing; the adoption of techniques and research around using wood for environmentally friendly composite production and the positive impact of this on the environment; wood's interaction with solid substances and with different mechanical loads, chemicals, and other substances; and the different forms of energy and surface modification of wood and wood composites.